Comunicación entre padres separados y su influencia en la estabilidad emocional de un niño - Chuchuca Espinoza, Karen Liseth (2020)
The objective of this case study was to identify the communication between separated parents and its influence on the emotional stability of a 10-year-old child, who has presented a strong emotional alteration generating a mental imbalance that is causing problems in his personal, family environment, social and academic. In many actions, parents are the cause of generating this type of problems in children unconsciously, by not reflecting that parents are the fundamental pillar for the optimal development of the child's emotional health, since parents are the ones who are forming the child from growth to adulthood. Reason why in this case study the knowledge that has been acquired in the course of the university career was applied using methods, techniques and tools for the identification of this problem, which was approached with the cognitive behavioral approach, being This is a brief technique which I apply to him in the time established for the investigation and emphasize that it gives results, it was a better one in his emotional state since I can identify his emotions and feelings in a better way.